SOCIAL OBSTACLES AFFECTING STUDENTS’ ACADEMIC ACHIEVEMENT AND PROPOSED TREATMNTS IN THE UAE: A STUDY OF ZAYED THE FIRST SCHOOL - Abdul Rahman, Asma; Almazroui, Karima; Abdul Rahman, Maryam; Alomairini, Mohammad; Hatta, Maryam Mohd (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study examines the impact of social obstacles on the academic achievement of third-cycle student in the United Arab Emirates (UAE) and proposes solutions to address these challenges. Using a social survey methodology, data were collected via a questionnaire at Zayed the First School in Abu Dhabi, involving 73 participants, including students, teachers, families, and staff. The study categorizes obstacles into cultural, familial, professional, and self-imposed barriers, highlighting key issues. This includes strained student-teacher relationships, bullying, excessive academic workloads, and extended study hours, negatively impacting students’ academic and social development. Additionally, the lack of cultural awareness among some expatriate teachers and family challenges, including neglect, overprotection, or disintegration, undermined students’ self-confidence and engagement. The study emphasizes the need for a holistic educational framework that prioritizes students’ emotional and social well-being alongside academic growth. Schools must function as socio-educational institutions, fostering collaboration between families and educators to create a supportive and culturally sensitive environment. Open communication is critical for addressing challenges, reinforcing positive behaviours, and ensuring alignment in supporting students. The findings advocate for strategic interventions to enhance social cohesion, emotional support, and cultural understanding, enabling students to thrive academically and socially within a nurturing educational ecosystem.